The Nurse as Patient Advocate - Bernal, Ellen W. (The Hastings Center report, 1992)
The claim that nurses should be patient advocates is a questionable one, especially when it is mixed in with the professional issue of nurses' freedom to practice. A less combative, more cooperative model of the profession would serve nurses better.